Winter hardiness and biometric indices of introduced strawberry cultivars under plastic film greenhouse conditions in Leningrad Province - S. F. Loginova (Труды по прикладной ботанике, генетике и селекции)
Background. The intensive inflow of strawberry cultivars from abroad in recent years and a great number of cultivation practices make an accelerated comprehensive study of these cultivars in new soil and climate conditions a high priority for the Northwest of the Russian Federation. Materials and methods. In 2016–2017, 35 newly introduced strawberry cultivars were studied at St. Petersburg State Agrarian University according to the Program and Methodology of Variety Research on Fruit, Berry and Nut Crops. The primary study focused on the biometric characteristics of strawberry cultivars, their winter hardiness, performance of the full cycle of phenological stages in plant development, resistance to spider mite, and productivity. These are the main criteria for cultivars to be grown in plastic film greenhouses in Leningrad Province. Results and conclusion. The primary study of the introduced cultivars under plastic film greenhouse conditions in Leningrad Province and their evaluation for winter hardiness, productivity and spider mite resistance made it possible to identify the cultivars ‘Vechnaya Vesna’, ‘Vystavochnaya’, ‘Yubileynaya Govorovoy’ ‘Jive’, ‘Diamante’ and ‘Elianny’ as promising for cultivation. They require further research targeted at a set of economically important traits.